DEVELOPING A MARKETING STRATEGY USING SWOT ANALYSIS IN THE DIGITAL ERA ON MOOI DONUT MSMES ON KALIMANTAN STREET, SUMBERSARI DISTRICT, JEMBER REGENCY - Fitria, Aulia ul; Izzuddin, Ahmad; Tyas, Wenny Murtalining (Universitas Muhammadiyah Tangerang, 2024)
Study aims to analyse the strategies to enchance the sales of Donat Mooi, a micro, small, and medium enterprise (MSME), in the digital era where consumers are increasingly adopting online purchasing. The study proposes using SWOT analysis as a strategy to address competition and improve the business's competitiveness. The focus is on identifying effective marketing alternatives to overcome challenges faced by Donat Mooi. The qualitative-descriptive method use with direct interviews, observations also literature reviews. It shows from SWOT analysis and Internal-External Matrix indicate the Donat Mooi currently holds a